An Experimental Study of Fracture Parameters of Concrete Produced With Basalt Aggregate by Peak-Load Method - Senem Yilmaz Cetin; Tahir Azad Celik (Advances in Civil Engineering)
Limestone or river aggregates have been traditionally used as aggregates in ready-mixed concrete from the past to the present. The depletion of these natural aggregates used in ready-mixed concrete has led the concrete industry to investigate aggregate resources and search for alternative aggregates. In this study, natural rocks defined as basalt type from Karacadağ, located within the borders of Diyarbakır, Şanlıurfa, and Mardin provinces in the Southeastern Anatolia Region of Türkiye, were used as aggregate materials. The mechanical strength of concrete produced with basalt aggregate was examined. In order to determine the physical and mechanical properties of the produced basalt aggregate concretes, unit weight, compressive strength, and splitting tensile strength experiments were carried out on hardened concretes. In addition to the physical and mechanical properties of basalts, their chemical composition properties have been investigated. In the experimental study, crushed basalt aggregates with size fractions 0–5, 5–11.2, and 11.2–22.4 mm were used. The water/cement ratio of the concrete produced in the study was 0.45, and the selected cement contents were determined as 300 kg/m3, 350, and 400 kg/m3. The fracture parameters of the produced concrete were presented with the two-parameter fracture model (TPFM). Statistical analyses of this study show that the fracture parameters of cube samples made with basalt aggregate commonly found in the region are acceptable for use in construction sites.